THE COMPARISON BETWEEN SCIENCE VIRTUAL AND PAPER BASED TEST IN MEASURING GRADE 7 STUDENTS' CRITICAL THINKING - Dhitareka, Putra Habib (2017)
This research was comparing science virtual and paper-based test in measuring grade 7 students' critical thinking based on Multiple Intelligences and gender. Quasi experimental method with within-subjects non-experimental design was conducted in this research in order to obtain the data. The population of this research was all seventh grade students in ten classes of one public secondary school in Bandung. There were 71 students within two classes taken randomly became the sample in this research. The data are obtained through 28 questions with a topic of living things and environmental sustainability that constructed based on eight critical thinking elements proposed by Inch and then the questions provided in science virtual and paper-based test. The data was analyzed by using paired-samples t test when the data are parametric and Wilcoxon signed ranks test when the data are non-parametric. In general comparison, the p-value of the comparison between science virtual and paper-based tests' score is 0.506, indicated that there are no significance difference between science virtual and paper-based test based on the tests' score. Furthermore, the Asymp. Sig. Values resulted from the comparison based on Multiple Intelligences are 0.935 for naturalist, 0.074 for musical, 0.654 for logical, 0.877 for existential, 0.329 for interpersonal, 0.129 for kinesthetic, 0.055 for verbal, 0.781 for intrapersonal, and 0.722 for visual intelligences, thus indicated that there is also no significance difference between science virtual and paper-based test based on students' Multiple Intelligences. Moreover, the p-values resulted from the comparison based on gender are 0.758 for male and 0.540 for female, this is also indicated that there is no significance difference based on gender. The results are furthermore supported by the students' attitude result which is 3.15 from the scale from 1 to 4, indicated that they have positive attitudes towards science virtual test. Moreover, teachers involved in this research were interviewed to know how their perspectives towards science virtual test is, and they agree that computer-based test like science virtual test are far beyond the limitation of paper-based test and expected similar test to be implemented as the common assessment tool as it provides many advantages. ;---Penelitian ini membandingkan Science Virtual Test dan tes berbasis kertas dalam mengukur kemampuan berpikir kritis siswa kelas 7 berdasarkan kecerdasan majemuk dan jenis kelamin. Metode non eksperimen/kuasi eksperimen dengan design within-subjects dilakukan dalam penelitian ini untuk mendapatkan data. Populasi penelitian ini adalah semua siswa kelas tujuh di sepuluh kelas salah satu SMP negeri di Bandung. Ada 71 siswa dalam dua kelas yang diambil secara acak menjadi sampel dalam penelitian ini. Data dalam penelitian ini diperoleh melalui 28 pertanyaan dengan topik makhluk hidup dan kelestarian lingkungan yang dibangun berdasarkan delapan elemen berpikir kritis yang di ajukan oleh Inch dan kemudian diintegrasikan dalam Science Virtual Test dan tes berbasis kertas. Data dianalisis dengan menggunakan paired-samples t test apabila data bersifat parametrik dan Wilcoxon signed rank test bila data bersifat non-parametrik. Dalam perbandingan secara umum, nilai p dari perbandingan antara nilai ujian Science Virtual Test dan tes berbasis kertas adalah 0,506, menunjukkan bahwa tidak ada perbedaan yang signifikan antara Science Virtual Test dan tes berbasis kertas berdasarkan skor tes. Selanjutnya, Asymp. Sig. Nilai yang dihasilkan dari perbandingan berdasarkan Multiple Intelligences adalah 0,935 untuk naturalis, 0,074 untuk musikal, 0,654 untuk logika, 0,877 untuk eksistensial, 0,329 untuk interpersonal, 0,199 untuk kinestetik, 0,055 untuk verbal, 0,781 untuk intrapersonal, dan 0,722 untuk kecerdasan visual, sehingga ditunjukkan bahwa tidak ada perbedaan signifikan antara Science Virtual Test dan berbasis kertas berdasarkan Multiple Intelligences siswa. Selain itu, nilai p yang dihasilkan dari perbandingan berdasarkan jenis kelamin adalah 0,758 untuk laki-laki dan 0,540 untuk perempuan, hal ini juga menunjukkan bahwa tidak ada perbedaan signifikan berdasarkan jenis kelamin. Hasil penelitian ini selanjutnya didukung oleh hasil kuesioner sikap siswa terhadap Science Virtual Test yaitu 3,15 dari skala 1 sampai 4, menunjukkan bahwa mereka memiliki sikap positif terhadap Science Virtual Test. Selain itu, para guru yang terlibat dalam penelitian ini diwawancarai untuk mengetahui bagaimana perspektif mereka terhadap Science Virtual Test, dan mereka setuju bahwa tes berbasis komputer seperti Science Virtual Test jauh melampaui batasan tes berbasis kertas dan tes serupa diharapkan untuk dapat diterapkan sebagai tes secara umum karena memberikan lebih banyak keuntungan dibanding tes berbasis kertas.